Academic Reading and Writing Challenges Among International EFL Master’s Students in a Malaysian University: The Voice of Lecturers - Kaur Mehar Singh, Manjet (Journal of International Students, 2019)
Focusing on the perspective of lecturers, this qualitative research investigated the academic reading and writing challenges faced by international English-as-a-foreign-language master’s students at a Malaysian university. Data was collected through semi-structured, in-depth, one-on-one interviews with 16 lecturers who taught international students from various graduate programs. The findings from the lecturers’ perspectives indicate that the students faced acute challenges in their academic reading and writing practices such as adhering to academic writing conventions and interpreting text in an English language instructional setting. This study suggests policies and programs to overcome the challenges of the international EFL students’ academic writing and reading practices to ensure their academic success in as they learn in graduate programs.